Inovasi Produk Opak Moronyoy Potensi Usaha Ekonomi Desa Karang Pakuan - Eri Sarimanah; Mohammad Syaiful; Asep Muhammad Ramdan (Bandung Conference Series: Economics Studies, 2024)
Abstract. Karangpakuan Village, located in Darmaraja District, Sumedang Regency, is one of the villages that still upholds local wisdom. It is characterized as a producer of traditional glutinous rice-based processed food, namely Opak, called Opak Moronyoy. This product has gained its own place in the local market and is able to attract consumers from various circles. This article is the output of the community service activities carried out by professors, supervisors, and students. The community service activities consist of activity planning, formulation of assistance activities, program assistance (innovation process), and innovation creation. The analysis method used is descriptive analytic, which is a method that focuses on the description that occurs in the community related to the object of community service in Karangpakuan Village in developing Opak Moronyoy MSMEs as an improvement in product quality and quantity. The results of the analysis include the benefits and constraints in activating MSMEs. The service team also provided suggestions regarding packaging design and packaging trials that are more modern and attractive to attract consumers widely. Abstrak. Desa Karangpakuan yang terletak di Kecamatan Darmaraja Kabupaten Sumedang merupakan salah satu desa yang masih menjunjung kearifan lokal. Memiliki ciri khas sebagai penghasil makanan olahan tradisional berbahan dasar ketan yakni Opak, yang bernama Opak Moronyoy. Produk ini telah memperoleh tempat tersendiri di pasar lokal dan mampu menggaet minat konsumen dari berbagai kalangan. Artikel ini merupakan luaran kegiatan Pengabdian kepada Masyarakat (PkM) yang dilakukan oleh guru besar, dosen pembimbing, dan mahasiswa. Aktivitas pengabdian terdiri dari perencanaan kegiatan, perumusan aktivitas pendampingan, pendampingan program (proses inovasi), sampai dengan cipta inovasi. Metode analisis yang digunakan adalah deskriptif analitik, yaitu sebuah metode berfokus pada deskripsi yang terjadi di masyarakat berkaitan dengan objek pengabdian prilaku masyarakat Desa Karangpakuan dalam mengembangkan UMKM Opak Moronyoy sebagai peningkatan kualitas dan kuantitas produk. Hasil analisis antara lain mengenai manfaat dan kendala dalam menggiatkan UMKM. Tim pengabdian juga memberikan usulan mengenai desain kemasan dan uji coba pengemasan yang lebih modern serta menarik untuk menggaet konsumen secara luas.